Role Stress And Compensation As Determinants Of Job Satisfaction Among Islamic Bank Employees In Banda Aceh City - Yulindawati, Yulindawati; Riza, Akmal; Lufita, Nina (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Companies that assign workloads exceeding normal practices inevitably increase employees work burdens and lead employees to choose overtime in order to complete these tasks. High job demands tend to cause employees to experience stress. This condition should therefore be balanced with appropriate compensation provided by the company so that employees feel satisfied in their work. The purpose of this study is to examine the effect of role stress and compensation variables on employee job satisfaction at an Islamic bank in Banda Aceh City. The methodology employed a quantitative approach with an associative research design. A total of 61 employees of the Islamic bank were selected as the sample using random sampling techniques. Primary data were collected through questionnaires, and multiple linear regression analysis was used to test the research hypotheses. The results of the study indicate that role stress and compensation have a significant effect on employee job satisfaction at the Islamic bank in Banda Aceh City.